Water Salinity in Agriculture: Analyzing Irrigation Water Quality for Farmers - Saludo, Ellysa Mae F.; Lagado, Maricel F.; Jose, Aaliyah Marie A. San; Agustin, Carmela P.; Lipardo, Nikka Joyce G.; Agustin, Michelle A. (International Journal of Environment, Engineering and Education, 2023)
The primary aim of this study is to assess irrigation water's salinity levels and categorize them as regular, slightly to moderately saline, or severely saline, using the salinity parameters established by Ayers and Westcot as a reference. This practice plays a substantial role in global agriculture, accounting for 20% of total cultivated land and contributing 40% of the world's food production. It falls under the classification of water usage known as Class C, which encompasses Fishery Water for the propagation and growth of aquatic resources, Recreational Water Class II for boating and similar activities, and Agriculture, including irrigation and livestock watering. This classification underscores irrigation water's profound influence on agriculture as a whole. Salinity, often considered one of humanity's earliest environmental challenges, is paramount. Excessive salinity in agriculture, particularly in the context of rice (Oryza sativa L.) cultivation, a staple crop that nourishes half of the global population, poses a formidable threat. High salinity levels can potentially hinder plant growth, reduce crop yields, and compromise the quality of agricultural products. This research seeks to illuminate the critical issue of salinity in irrigation, specifically focusing on its implications for rice cultivation, which plays a pivotal role in global food security. By delineating the salinity status of irrigation water, it aims to provide valuable insights into the challenges confronted by agricultural communities and lay the groundwork for informed decision-making in sustainable agriculture.